A novel scoring system for the quantitative prediction of prognosis in acute myeloid leukemia - Yu, Yang; Wang, Hao; Yang, Jing-Jing; Fang, Shu; Wen, Ya-Nan; Jiao, Yi-Fan; Qian, Kun; Le, Ning; Shan, Ruo-Qi; Gao, Wen-Jing; Hua, Bao-Lai; Li, Fei (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is a heterogeneous hematopoietic malignancy. Patient prognosis cannot be accurately assessed in National Comprehensive Cancer Network (NCCN) risk stratification subgroups based on the current criteria. This study aimed to develop a novel prognostic score model for the quantitative prediction of prognosis in AML. We developed a prognostic risk scoring model of AML using differentially expressed genes to predict prognosis in patients with AML. Furthermore, we evaluated the effectiveness and clinical significance of this prognostic model in 4 AML cohorts and 905 patients with AML. A prognostic risk scoring model of AML containing eight prognosis-related genes was constructed using a multivariate Cox regression model. The model had a higher predictive value for the prognosis of AML in the training and validation sets. In addition, patients with lower scores had significantly better overall survival (OS) and even-free survival (EFS) than those with higher scores among patients with intermediate-risk AML according to the NCCN guidelines, indicating that the model could be used to further predict the prognosis of the intermediate-risk AML populations. Similarly, patients with high scores had remarkably poor OS and EFS in the normal-karyotype populations, indicating that the scoring model had an excellent predictive performance for patients with AML having normal karyotype. Our study provided an individualized prognostic risk score model that could predict the prognosis of patients with AML.